2016
DOI: 10.2500/ajra.2016.30.4298
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Effectiveness of Perioperative Prophylactic Antibiotics for Skull Base Surgeries

Abstract: Despite institutional variability in antibiotic regimens, meningitis rarely occurs after skull base procedures and seems to be encountered most frequently in open craniofacial surgeries. A systematic review revealed a limited number of published studies, all observational in study design, which precluded a formal meta-analysis. A novel large-scale randomized-controlled clinical trial is needed to evaluate antibiotic selection and need in endoscopic skull base surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
0
21
0
3
Order By: Relevance
“…Scant literature exists regarding antibiotic prophylaxis in ESBS and no existing data suggest the superiority of one regimen over another in ESBS. [28][29][30][31] Regardless of antibiotic choice, infectious complications such as meningitis remain rare and are associated with postoperative CSF leak. 28,29,32 One prior study suggested 24 to 48 hours of a single agent covering gram-positive organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scant literature exists regarding antibiotic prophylaxis in ESBS and no existing data suggest the superiority of one regimen over another in ESBS. [28][29][30][31] Regardless of antibiotic choice, infectious complications such as meningitis remain rare and are associated with postoperative CSF leak. 28,29,32 One prior study suggested 24 to 48 hours of a single agent covering gram-positive organisms.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] Regardless of antibiotic choice, infectious complications such as meningitis remain rare and are associated with postoperative CSF leak. 28,29,32 One prior study suggested 24 to 48 hours of a single agent covering gram-positive organisms. 32 Another study recommended two doses of cefuroxime was adequate for transsphenoidal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of nasal packing was not assessed as an independent factor for outcomes including infectious complications. The 2016 systematic review by Rosen et al . did not find any evidence linking the use of nasal packing or the duration of nasal packing to infectious complications or duration of antibiotics.…”
Section: Intraoperative Considerationsmentioning
confidence: 98%
“…Two of the studies did not have exclusion criteria, the other 2 studies excluded patients felt to be at elevated risk of postoperative complications . In addition, there was a systematic review of open, microscopic, and endoscopic approaches to the skull base, which included the studies listed here that had been published at that time . However, the authors were not able to perform a meta‐analysis given the heterogeneity of the studies.…”
Section: Intraoperative Considerationsmentioning
confidence: 99%
“…Miller et al 12 review data that analyzes the impact of middle turbinate resection on bleeding after ESS and conclude that there is no change in major bleeding risk but that patients on anticoagulants are at an increased risk of minor bleeds after surgery. Rosen et al 13 conducted a systematic review of antibiotic use in endoscopic skull base surgery and show that, in general, meningitis is exceedingly rare in endoscopic relative to open procedures. The article by Zelenik et al 14 adds to the ongoing controversy regarding the association between esophageal reflux and CRS.…”
mentioning
confidence: 99%